Prevalence of Depression, Anxiety and Stress among Chronic Kidney Disease Patients Undergoing Hemodialysis - Sharma, Pujan; Raut, Raju; Koirala, Samikshya; Sharma, Narayan Prasad (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Patients with chronic kidney disease (CKD) undergoing hemodialysis often experience significant psychological distress, which can adversely affect treatment adherence and quality of life. However, limited studies in Nepal have explored the mental health status of this population. This study aimed to assess the prevalence of depression, anxiety, and stress among CKD patients undergoing hemodialysis and to examine their association with selected socio-demographic and clinical factors. Method: A cross-sectional study was conducted among 143 patients undergoing hemodialysis at Manmohan Memorial Teaching Hospital, Kathmandu. Data were collected using a socio-demographic questionnaire and the Nepali version of the Depression, Anxiety and Stress Scale (DASS-21). Descriptive statistics, correlation, and chi-square tests were used for data analysis. Results: A considerable proportion of participants reported moderate levels of depression, anxiety, and stress. Education level showed a significant negative correlation with all three psychological outcomes, indicating that patients with lower education experienced higher emotional distress. Gender, duration of dialysis, and comorbid diabetes were not significantly associated with mental health outcomes, although female patients reported slightly higher depressive symptoms. Conclusion: The study reveals a high prevalence of depression, anxiety, and stress among CKD patients on hemodialysis, highlighting the need for regular mental health screening and psychosocial support in dialysis care.